2007
DOI: 10.1097/gim.0b013e31815bf953
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians' concerns about offering a genetic test to tailor smoking cessation treatment

Abstract: Purpose:We assessed the importance assigned by primary care physicians to eight factors influencing whether they would order a genetic test to individually tailor smoking cessation treatment. Methods: A random sample of United States primary care physicians was surveyed about how important each of eight factors were in the decision to order the test. Broadly, these factors included the ability of the test to improve treatment, the patient's reaction to test results, concern about misuse of test results, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…These findings contrast with European and U.K. health professional concerns about patient harms, pressure, and access (Rogausch et al, 2006;Fargher et al, 2007a;Hoop et al, 2010). However, similar concerns about uncertain clinical utility have been noted with respect to disease-based testing (Escher and Sappino, 2000;Mountcastle-Shah and Holtzman, 2000;Freedman et al, 2003;Levy et al, 2007;Park et al, 2007). Despite these concerns, other studies have found a high likelihood of use of new genetic tests such as PGx testing among PCPs (Park et al, 2007;Shields et al, 2008) and early adopters (Fargher et al, 2007b;Hoop et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…These findings contrast with European and U.K. health professional concerns about patient harms, pressure, and access (Rogausch et al, 2006;Fargher et al, 2007a;Hoop et al, 2010). However, similar concerns about uncertain clinical utility have been noted with respect to disease-based testing (Escher and Sappino, 2000;Mountcastle-Shah and Holtzman, 2000;Freedman et al, 2003;Levy et al, 2007;Park et al, 2007). Despite these concerns, other studies have found a high likelihood of use of new genetic tests such as PGx testing among PCPs (Park et al, 2007;Shields et al, 2008) and early adopters (Fargher et al, 2007b;Hoop et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Low perceived clinical utility, as well as concerns about potential discrimination, have repeatedly been reported as primary barriers to uptake of both traditional genetic testing and newer applications [35][36][37][38][39] . Similarly, we found that uncertain clinical utility was among the top concerns of respondents for themselves and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large number of CYP2A6 alleles, genotyping to characterize inherited differences in nicotine metabolism can be much more costly than testing for the NMR, which can be determined from blood or saliva for approximately US$50 per sample (Lerman et al 2015). Lastly, primary care physicians may be less inclined to offer a genetic test compared to a phenotypic biomarker; these concerns may relate in part to lack of knowledge about genetics and concerns about the sensitivity of genetic information (Levy et al 2007; Shields et al 2008). …”
Section: The Nicotine Metabolite Ratio As a Biomarker Of Nicotinementioning
confidence: 99%